Strategies to Inhibit Myc and Their Clinical Applicability - Whitfield, Jonathan R.; Beaulieu, Marie-Eve; Soucek, Laura (Frontiers in Cell and Developmental Biology, 2017)
Myc is an oncogene deregulated in most – perhaps all – human cancers. Each Myc family member, c-, L- and N-Myc, has been connected to tumour progression and maintenance. Myc is recognised as a ‘most wanted’ target for cancer therapy, but has for many years been considered undruggable, mainly due to its nuclear localization, lack of a defined ligand binding site, and physiological function essential to the maintenance of normal tissues. The challenge of identifying a pharmacophore capable of overcoming these hurdles is reflected in the current absence of a clinically-viable Myc inhibitor. The first attempts to inhibit Myc used antisense technology some three decades ago, followed by small molecule inhibitors discovered through ‘classical’ compound library screens. Notable breakthroughs proving the feasibility of systemic Myc inhibition were made with the Myc dominant negative mutant Omomyc, showing both the great promise in targeting this infamous oncogene for cancer treatment as well as allaying fears about the deleterious side effects that Myc inhibition might have on normal proliferating tissues. During this time many other strategies have appeared in an attempt to drug the undruggable, including direct and indirect targeting, knockdown, protein/protein and DNA interaction inhibitors, and translation and expression regulation. The inhibitors range from traditional small molecules to natural chemicals, to RNA and antisense, to peptides and miniproteins. Here, we briefly describe the many approaches been taken so far, with a particular focus on their potential clinical applicability.